1984
DOI: 10.1007/bf02678782
|View full text |Cite
|
Sign up to set email alerts
|

Development of new crops for industrial raw materials

Abstract: Commercial fats and oils are still used extensively in chemical manufacturing processes, but their fatty acid compositions are limited in variety. An extensive screening program for potential new oilseed crops has led to the discovery of many good sources of new lipid classes and fatty acids. Among them are long‐chain acids (Crambe, Limnanthes, Lunaria), medium‐chain acids (Cuphea, Umbelliferae, Lauraceae), hydroxy acids (Lesquerella), epoxy acids (Vernonia, Stokesia), acids with special unsaturation (conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 26 publications
1
26
1
1
Order By: Relevance
“…The results of planting date from October to November indicated that the later it was planted the fewer its primary branches, seeds per plant and 1000 seeds weight were, and the percentage of 212 -224, which its blooming date was around March and harvest date, early May. This differed greatly from the result of 90 -105 days reported previously (Princen, 1984). Whereas when C. abyssinica was planted in Kunming in the early June, it has a life cycle of 100 days but frequently resulted in low yields (Table 1).…”
Section: Planting Datecontrasting
confidence: 54%
“…The results of planting date from October to November indicated that the later it was planted the fewer its primary branches, seeds per plant and 1000 seeds weight were, and the percentage of 212 -224, which its blooming date was around March and harvest date, early May. This differed greatly from the result of 90 -105 days reported previously (Princen, 1984). Whereas when C. abyssinica was planted in Kunming in the early June, it has a life cycle of 100 days but frequently resulted in low yields (Table 1).…”
Section: Planting Datecontrasting
confidence: 54%
“…Dans ses projets, l'US department of Agriculture a privilégié les huiles nouvelles sources d'acides gras particuliers, potentiellement utilisables par l'industrie (Earle et al, 1959 ;Isbell, 2009 ;Princen et Rothfus , 1984), relativisant ainsi l'importance du screening systématique des années 1950 (Earle et al, 1959). Salas et al (2009) Le traitement le plus original de la question est dû à Dubois et al (2008), avec un classement des sources végé-tales d'acides gras en fonction de leur profil nutritionnel, qui, non seulement considère les quantités des acides gras individuels, mais prend également en compte l'environnement en AG, de ces majeurs, sous forme de profil AG matérialisés par des radar-plots.…”
Section: Plantes à Teneur Moyenne En Matière Grasseunclassified
“…Every plant collection should be moreover documented by a reference specimen. If it is possible, the collection at different places should be considered to recognize eventual genetic variations [29].…”
Section: General Remarks On Screening Analysismentioning
confidence: 99%
“…Recently, the interest in fatty acids with unusual structure features and in oils, that can provide a high concentration of a single fatty acid, has increased as they can be of high value for the chemical and pharmaceutical industry [28][29][30][31][32][33]. Global screening programs for the search of new plant oils as renewable sources have been initiated.…”
Section: Introductionmentioning
confidence: 99%